IMF Survey, Volume 37, Issue 07. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2008)
Inflation, IMF work agenda, Food and fuel prices, Commodity price surge, Oil price surge, Jeddah meeting, Haiti interview, Norway's sovereign wealth fund, Mexico, Switzerland's monetary policy, Mauritius, News briefs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet